Sickness-certification practice in different clinical settings; a survey of all physicians in a country - Ekmer Anna; Skånér Ylva; Hinas Elin; Löfgren Anna; Nilsson Gunnar; Arrelöv Britt; Lindholm Christina; Alexanderson Kristina (BMC, 2010)
Abstract Background How physicians handle sickness-certification is essential in the sickness-absence process. Few studies have focused this task of physicians' daily work. Most previous studies have only included general practitioners. However, a previous study indicated that this is a common task also among other physicians. The aim of this study was to gain detailed knowledge about physicians' work with sickness-certification and of the problems they experience in this work. Methods A comprehensive questionnaire regarding sickness-certification practice was sent home to all physicians living and working in Sweden (N = 36,898; response rate: 61%). This study included physicians aged <65 years who had sickness-certification consultations at least a few times a year (n = 14,210). Descriptive statistics were calculated and odds ratios (OR) with 95 % confidence intervals (CI) were estimated for having different types of related problems, stratified on clinical settings, using physicians working in internal medicine as reference group. Results Sickness-certification consultations were frequent; 67% of all physicians had such, and of those, 83% had that at least once a week. The proportion who had such consultations >5 times a week varied between clinical settings; from 3% in dermatology to 79% in orthopaedics; and was 43% in primary health care. The OR for finding sickness-certification tasks problematic was highest among the physicians working in primary health care (OR 3.3; CI 2.9-3.7) and rheumatology clinics (OR 2.6; CI 1.9-3.5). About 60% found it problematic to assess patients' work capacity and to provide a prognosis regarding the duration of work incapacity. Conclusions So far, most interventions regarding physicians' sickness-certification practices have been targeted towards primary health care and general practitioners. Our results indicate that the ORs for finding these tasks problematic were highest in primary health care. Nevertheless, physicians in some other clinical settings more often have such consultations and many of them also find these tasks problematic, e.g. in rheumatology, neurology, psychiatry, and orthopaedic clinics. Thus, the results indicate that much can be gained through focusing on physicians in other types of clinics as well, when planning interventions to improve sickness-certification practice.